POLYSACCHARIDE KRESTIN ACTIVITY FROM Coriolus versicolor EXTRACT AGAINST PHAGOCYTOSIS ABILITY ON MICE INFECTED BY Staphylococcus aureus - Nadyatul Ilma Indah Savira; Sri Puji Astuti Wahyuningsih; Dewi Rahmawati (BIOEDUKASI, 2021)
Staphylococcus aureus is an opportunistic pathogen and cause of nosocomial infection, which has leukocidin and can reduce immunity. Because of antibiotic resistance, immunomodulator is an alternative treatment for S. aureus infection. Polysaccharide krestin (PSK) from Coriolus versicolor extract contains active β-glucan that triggers immune responses' effectiveness including phagocytosis. This research aimed to know the activity of PSK against phagocytosis ability on mice infected by S. aureus. There were six treatment groups. 100 mg/kg BW PSK was given to the mice strain Balb/C by gavage. S. aureus was infected once every two weeks. Phagocytosis ability consisted of phagocytic activity and capacity, counted on slide smears of mice intraperitoneal fluid. The results showed that PSK increased phagocytic activity in the group giving PSK after infection. Furthermore, the most effective giving PSK on phagocytic capacity was before and after infection. Based on this research, PSK increased immunity by phagocytosis ability and can be useful as an immunomodulator.